2022
DOI: 10.1186/s40981-022-00498-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasma orexin A does not reflect severity of illness in the intensive care units patients with systemic inflammation

Abstract: Background Systemic inflammatory response occurs by sepsis and invasive surgery. Recent articles suggest that not only CRP but also procalcitonin, presepsin, and neutrophil gelatinase-associated lipocalin may reflect the severity of systemic inflammation. In addition, as systemic inflammation could degenerate orexin neurons, plasma orexin A might also be a good biomarker to predict the severity. Thus, we have determined relation between plasma biomarker and severity of illness score in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…However, from the results of this study, it may be difficult to assess systemic inflammation based on blood orexin. Indeed, it has been reported that blood orexin does not reflect the severity of illness in intensive care unit patients with systemic inflammation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, from the results of this study, it may be difficult to assess systemic inflammation based on blood orexin. Indeed, it has been reported that blood orexin does not reflect the severity of illness in intensive care unit patients with systemic inflammation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%